1997
DOI: 10.1108/eum0000000004418
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term strategic management in mass customized markets

Abstract: Explains that globalization and new manufacturing technologies have been generating a new kind of product competition based on the ability of the producer to offer the most suitable product for each individual market. In this new environment, the relationship between short‐term logistical decisions taken within manufacturing and business performance becomes increasingly strong. This relationship can also be complex, owing to the large number of variables and trade‐offs within the decision process. Manufacturin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…This was marked by the entry of global players in the local market and intensification of competition (Gunasekaran et al, 2008;Jagadeesh, 1999). As a result, the customers were not just content with the quality of the products and services rather they began to demand varieties (Zhang et al, 2009;Sherehiy et al, 2007;Saisse and Wilding, 1997). The uniformity of preferences among the customers also began to vanish.…”
Section: Introductionmentioning
confidence: 92%
“…This was marked by the entry of global players in the local market and intensification of competition (Gunasekaran et al, 2008;Jagadeesh, 1999). As a result, the customers were not just content with the quality of the products and services rather they began to demand varieties (Zhang et al, 2009;Sherehiy et al, 2007;Saisse and Wilding, 1997). The uniformity of preferences among the customers also began to vanish.…”
Section: Introductionmentioning
confidence: 92%
“…AM calls for the manufacturing companies to respond to individual customer's dynamic demands (Saisse and Wilding 1997). Thus, both AM and MC are adopted to meet the requirements and aspirations of individual customers (Bardakci andWhitelock 2003, Jin-Hai et al 2003).…”
Section: Introductionmentioning
confidence: 98%
“…This kind of turbulence is very likely to occur when manufactured products have short life cycles or go through numerous design changes within their life cycle. This is precisely the case in mass customised markets such as those the automotive industry is tending to [9].…”
Section: Instability In the Supply Chainmentioning
confidence: 99%
“…Wilding [14] has demonstrated that inventory control algorithms can generate chaos within simple supply chains. It should be emphasised that within chaotic systems, demand data, for example, can be forecast reasonably accurately in the short term; this further emphasises the need for effective short-term decision making, rather than long range planning [15].…”
Section: Insert Figure 3: the Turbulence Pipelinementioning
confidence: 99%